2023
DOI: 10.3390/w15163000
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Groundwater Depth on Vegetation Coverage in the Ulan Buh Desert in a Recent 20-Year Period

Ting Lu,
Jing Wu,
Yangchun Lu
et al.

Abstract: As a typical desert in the Inner Mongolia Autonomous Region, the Ulan Buh Desert has a dry climate and scarce precipitation all year round. Groundwater has become the main factor limiting the growth of vegetation in this region. It is of great significance to study the influence of groundwater depth on the spatial distribution pattern of vegetation in this region. Based on the PIE-Engine platform and using long-term time-series Landsat data, this paper analyzed the spatial–temporal distribution characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…Groundwater level fluctuation could reflect the groundwater process within aquifers and thus could provide insight into the correlations between groundwater and the local environment [12]. Land-cover change has significantly influenced groundwater levels and thus, in turn, affected natural vegetation in desert regions, such as cultivated land expansion, which has led to groundwater level decreasing and vegetation degradation in oasis-desert regions over the past decades [5,11,13,14]. This has seriously threatened the security of water resources, economies, and ecosystems in arid areas [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Groundwater level fluctuation could reflect the groundwater process within aquifers and thus could provide insight into the correlations between groundwater and the local environment [12]. Land-cover change has significantly influenced groundwater levels and thus, in turn, affected natural vegetation in desert regions, such as cultivated land expansion, which has led to groundwater level decreasing and vegetation degradation in oasis-desert regions over the past decades [5,11,13,14]. This has seriously threatened the security of water resources, economies, and ecosystems in arid areas [10].…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al [23] reported that the dynamic variations of groundwater level depth could largely control desert vegetation. Additionally, some studies have examined the characteristics of groundwater levels in the oases of Tarim Basin using multiple temporal scales [13,18,33]. Bai et al [18] reported that groundwater overexploitation was the dominant factor of groundwater level decline in the Yarkand River irrigation districts in China.…”
Section: Introductionmentioning
confidence: 99%